Geographical variation in hospitalization for psychosis associated with cannabis use and cannabis legalization in the United States: Submit to: Psychiatry Research. (February 2022) - Moran, Lauren V.; Tsang, Erica S.; Ongur, Dost; Hsu, John; Choi, May Y.
Highlights: Hospitalizations for psychosis/cannabis use more likely in areas where cannabis legalized. Recreational cannabis legalization associated with greater rate of hospitalization for psychosis associated with cannabis use. Findings warrant future longitudinal studies to evaluate psychosis in U.S. states. Abstract: The 2017 National Inpatient Sample database was utilized to investigate the association between cannabis legalization in the United States and hospitalizations for psychosis associated with cannabis use. We compared the odds of hospital discharges for psychosis associated with cannabis use in adults between the Pacific census division (where most states legalized recreational cannabis use) and other divisions using multivariable logistic regression, adjusting for confounders. We calculated a score for each census division representing cannabis legality as the population-weighted sum of state scores: 1=illegal or cannabidiol/low potency cannabis; 2= medical marijuana; and 3=recreational and medical marijuana legalized. Pearson's correlation coefficients (r) quantified the relationship between scores and the proportion of hospitalizations with psychosis associated with cannabis. In 2017, there were an estimated 129, 070 hospital discharges for psychosis associated with cannabis use. The Pacific census division had significantly higher odds of discharges than other divisions (adjusted odds ratio 1.55; 95% confidence interval 1.25 – 1.93). There was a significant correlation between the cannabis legality score and proportion of hospital discharges for psychosis associated with cannabis use ( r  = 0.67, p <0.05). In conclusion, we observed a higher proportion of hospital discharges for psychosis associated with cannabis use in areas with more liberal cannabis legalization laws.